Enhancement of the Photocatalytic Activity of Carbon Nitrides by Complex Templating. Issue 30 (17th June 2015) - Chen, Zu Peng; Antonietti, Markus; Dontsova, Dariya
Abstract Carbon nitrides with the increased surface areas (≈90 m2 g−1) were prepared by the heat‐treatment of melamine–[Al(NO3)3]⋅9 H2O complexes. Here, [Al(NO3)3]⋅9 H2O was successfully used as a "green template" and a hydrogen‐bonding partner of melamine, simultaneously providing a distinct porosity and defined particle morphology for the resulting carbon nitrides. The influence of the solvent and precursors ratio on the stoichiometry of the complexes, as well as the morphology, optical properties, and photocatalytic activity of resulting products for Rhodamine B degradation and sacrificial hydrogen evolution were investigated. We also studied the temperature‐induced transformations of the starting complex to access the reaction mechanism. The developed synthesis procedure results in a significantly increased photocatalytic activity (up to 20‐fold) compared with that of the ground reference material.